-3(m+2)+6m=9(m+-1)

Simple and best practice solution for -3(m+2)+6m=9(m+-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(m+2)+6m=9(m+-1) equation:


Simplifying
-3(m + 2) + 6m = 9(m + -1)

Reorder the terms:
-3(2 + m) + 6m = 9(m + -1)
(2 * -3 + m * -3) + 6m = 9(m + -1)
(-6 + -3m) + 6m = 9(m + -1)

Combine like terms: -3m + 6m = 3m
-6 + 3m = 9(m + -1)

Reorder the terms:
-6 + 3m = 9(-1 + m)
-6 + 3m = (-1 * 9 + m * 9)
-6 + 3m = (-9 + 9m)

Solving
-6 + 3m = -9 + 9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9m' to each side of the equation.
-6 + 3m + -9m = -9 + 9m + -9m

Combine like terms: 3m + -9m = -6m
-6 + -6m = -9 + 9m + -9m

Combine like terms: 9m + -9m = 0
-6 + -6m = -9 + 0
-6 + -6m = -9

Add '6' to each side of the equation.
-6 + 6 + -6m = -9 + 6

Combine like terms: -6 + 6 = 0
0 + -6m = -9 + 6
-6m = -9 + 6

Combine like terms: -9 + 6 = -3
-6m = -3

Divide each side by '-6'.
m = 0.5

Simplifying
m = 0.5

See similar equations:

| 9a+33ab+-76b+65c+17a+51ab+-80b+13c= | | 3+16x+12=11x+15+5x | | -2c+3.7=-0.5 | | 21ab+-50b+13c+17a+30ab+-30b= | | 6x-42=9x | | 12x+2=12x-5 | | 9a+12ab+-26b+52c+21ab+-50b+13c= | | 7*4x=x+8 | | 8x-72=5x+25 | | 15ab+-24b+17a+15ab+-6b= | | 7x+14x+21x+28x=360 | | 94+84+62+y=(4-2)180 | | 94+84+72+y=(4-2)180 | | -2(1+7x)= | | 3c*5a*2a+8= | | 6ab+-26b+13c+15ab+-24b= | | 15a+25b= | | 101+80+65+y=(4-2)180 | | 1-5n+1+3n= | | 101+80+75+y=(4-2)180 | | 9a+6ab+39c+6ab+-26b+13c= | | 10x-1=328 | | 15v-8v=28 | | 15v-18v=28 | | 74+89+98+y=(4-2)180 | | 13ab+-7b+17a+2ab+b= | | 3(4x+9)-6x=0 | | 42=2w+16 | | 3X=1-y-4z | | 2x+4x+6x+8x=360 | | 72+100+83+y=(4-2)180 | | 2ab+-17b+13ab+-7b= |

Equations solver categories